Edukasi Politik melalui Media Sosial: Kajian Tindak Tutur Representatif Ferry Irwandi di Instagram - Novelly, Yustitiayu; Indriyani, Vivi (Jurnal Komunitas Bahasa, 2025)
This study aims to examine how social media functions as a political education platform through the use of representative speech acts. This study employed a descriptive qualitative approach with representative speech act theory. Data were obtained from Ferry Irwandi's Instagram account (@irwandiferry) from January to August 2025. There were 35 posts focused on political and state issues in Indonesia. Data analysis revealed 145 representative speech acts. These representative speech acts comprised six forms: explaining, stating, showing, reminding, mentioning, and speculating. The results showed that explaining was the dominant representative speech act. These findings demonstrate that Ferry Irwandi strives to provide political insight, build understanding, foster public awareness, and encourage the public to be critical of government policies, rather than passively accepting them. The implications of this study confirm that social media, particularly Instagram, can be an effective platform for political literacy when used with argumentative, clear, and educative language strategies.